Urban food systems for better diets, nutrition, and health - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
Major shifts in our global food system, driven in part by rapid urbanization, threaten the urban poor's access to healthy diets and exacerbate malnutrition in all its forms.